The origin of introduced rainbow trout (Oncorhynchus mykiss) in the Santa Cruz River, Patagonia, Argentina, as inferred from mitochondrial DNA - Riva Rossi, Carla Marcela (2004)
Rainbow trout (Oncorhynchus mykiss) was first introduced into Argentinean Patagonia, the southernmostregion of South America, from the United States in 1904 and at present constitutes the most conspicuous freshwaterfish in lakes and rivers of the region. The Santa Cruz River in Southern Patagonia is the only river in the world wherea self-sustained population of introduced rainbow trout is known to have developed an anadromous run. In this study,we examined mtDNA sequence variation to identify the source of Santa Cruz River rainbow trout, providing a historicalframework to interpret the processes underlying phenotypic variation and structure of Patagonian populations. TheSanta Cruz River may harbor distinct North American stocks of rainbow trout, widely distributed around the worldduring the late 19th and early 20th centuries, but today threatened after decades of habitat loss, species introduction,and introgression from alien stocks. The mtDNA sequence data revealed that the most likely origin for wild anadromousand nonanadromous fish was the McCloud River in California. Meanwhile, a local hatchery stock, representativeof rainbow trout introduced from Denmark after 1950 and widely stocked ever since throughout Patagonia, most probablyoriginated from multiple lineages from western North America, including non-Californian populations.